ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI MOTIVASI SISWA KELAS V SD NEGERI 147 PEKANBARU MENGERJAKAN PEKERJAAN RUMAH (PR) - Lenny Elviyanti; Zariul Antosa; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low motivation of students in doing homework (homework) given by teachers at school. This study aims to determine the internal factors that influence students' motivation to do homework and the internal factors that most influence the motivation of students to do homework. This type of research is descriptive quantitative research. This research was conducted in class V SD Negeri 147 Pekanbaru. Based on the results of the study, it was found that internal factors that influence students 'motivation to do homework consist of, factors of students' aspirations or aspirations, factors of student ability and factors of student conditions. The internal factors that most influence the motivation of students in class V SD Negeri 147 Pekanbaru, namely the ideals or aspirations of students is 34.4%.Key Words: Internal Factors, Motivation, Homework.